Assessment of mothers' practices toward children with steroid – sensitive nephrotic syndrome at pediatrics hospitals in Baghdad city - Zyarah, Feryal; Mua’ala, iqbal (Iraqi National Journal of Nursing Specialties, 2011)
Objective(s): To assess mothers' practices toward children with steroid – sensitive Nephrotic Syndrome (SSNS) whoare visiting nephrology consultation units, and to find out the relationships between their practices and thedemographical data for mother and child.Methodology: A descriptive study was carried out at nephrology consultation units of Baghdad pediatrics hospitals(Child's Central Pediatric Teaching Hospital, Al-kadimiyia Teaching Hospital, and Welfare Teaching Hospital) startedfrom February 18th to the end of July 2009. A purposive sample of (80) mothers who company their children wereselected. The data were collected through a constructed questionnaire, with two parts; the first part is concerned withmother's and child's demographical characteristic, the second part is concerned with mothers' practices aboutsteroid– sensitive nephrotic syndrome. An interview method was used to full questionnaire format. The validity wasdetermined through a panel of experts. While, the reliability was determined through a pilot study. The data wereanalyzed by using descriptive and inferential statistical measures by using the statistical package of social science(SPSS) version (15).Results: The findings of the study showed that mothers have poor practices (61.3%). The study results revealed thatthere is a significant association between mothers' practices and their educational level, and duration of the child'sdisease. While mother's age, occupation, child's age, child's sex, child's age at onset (years), child's previous diseaseand heredity have no association with their practices.Recommendations: The study recommends that health education for mothers would improve their practices.